Die ontstaan van die Nederlandsche Bank en Credietvereeniging voor Zuid-Afrika, 1888 : vestigingsprobleme in perspektief Grietjie Verhoef Rand Afrikaans University Keywords: Zuid-Afrikaansche Republiek, Banks, Calkoen H.L., Nederlandsche Bank en Credietve (Historia, 2021)
The establishment of the Nederlandsche Bank en Credietvereeniging in South Africa. Establishment and further perspective. The Nederlandsche Bank en Credietvereeniging was established in the Zuid-Afrikaansche Republiek in 1888 amidst the attempts of the government to establish a national bank in the country. Several other banks had established themselves in the country, but the ZAR government was suspicious of them because of their imperial connections. The economic situation in the ZAR was very bad after the war of 1881-1882 and the government was seeking loyal financial institutions to support the reconstruction of the ZAR. The NB en CV was established as a Netherlands bank in Amsterdam, operating in the ZAR when they failed to obtain the concession for the national bank, it was nevertheless decided to remain operative in the ZAR. The bank had difficulties with managers in the ZAR, but once the management structure was formalised and functioning effectively, the bank achieved considerable success. The bank started with capital of ï¿½200 000, of which ï¿½50 000 was issued. The bank conducted the normal commercial banking business, but cautiously avoided involvement in the speculative gold industry. Insufficient working capital hampered the bank's activities throughout the period until 1902. Capital was put at the disposal of the NB en CV by its Amsterdam Management, but even that did not fully relieve the shortage of capital. By 1902 the bank had four branches in the ZAR and showed a comparatively higher annual compound growth in its deposits and loans and advances than the far bigger Standard Bank. The war caused the British authorities to ban the NB en CV Chief Agent from the Transvaal, but after 1902 the bank was allowed to continue its operations, although on a restricted basis.
Keywords: Zuid-Afrikaansche Republiek; Banks; Calkoen H.L.; Nederlandsche Bank en Credietvereniging; Financial institutions